Geologic context of geodetic data across a basin and range normal fault, Crescent Valley, Nevada - Sieh, Kerry (2012)
Geodetic strain and late Quaternary faulting in the Basin and Range province is distributed over a region much wider than historic seismicity, which is localized near the margins of the province. In the relatively aseismic interior, both the magnitude and direction of geodetic strain may be inconsistent with the Holocene faulting record. We document the best example of such a disagreement across the NE striking, ∼55° NW dipping Crescent normal fault, where a NW oriented, 70 km geodetic baseline records contemporary shortening of ∼2 mm/yr orthogonal to the fault trace. In contrast, our geomorphic, paleoseismic, and geochronologic analyses of the Crescent fault suggest that a large extensional rupture occurred during the late Holocene epoch. An excavation across the fault at Fourmile Canyon reveals that the most recent event occurred at 2.8 ± 0.1 ka, with net vertical tectonic displacement of 4.6 ± 0.4 m at this location, corresponding to the release of ∼3 m of accumulated NW-SE extension. Measured alluvial scarp profiles suggest a minimum rupture length of 30 km along the range front for the event, implying a moment magnitude Mw of at least 6.6. No prior event occurred between ∼2.8 ka and ∼6.4 ± 0.1 ka, the 14C calender age of strata near the base of the exposed section. Assuming typical slip rates for Basin and Range faults (∼0.3 mm/yr), these results imply that up to one third, or ∼1 m, of the extensional strain released in the previous earthquake could have reaccumulated across the fault since ∼2.8 ka. However, the contemporary shortening implies that the fault is unloading due to a transient process, whose duration is limited to between 6 years (geodetic recording time) and 2.8 ka (the age of the most recent event). These results emphasize the importance of providing accurate geologic data on the timescale of the earthquake cycle in order to evaluate geodetic measurements.